Teaching Learning Process of English At SMK Negeri 6 Surakarta: A Micro Ethnographic Approach - Hartuti, Hartuti; , Prof. Dr. Endang Fauziati, M. Hum; , Drs. Abdillah Nugroho, M.Hum (2013)
The objective of the research is to get a clear description of the teaching learning process of English at SMK Negeri 6 Surakarta in which covers about to know the objective of English teaching learning process, to know the syllabus used by teachers, to know the method of teaching in the classroom in which also covers about the role of materials, the classroom procedure, classroom activities, teacher‟s and learner‟s role, the media, and the evaluation. The research was conducted in Sekolah Menengah Kejuruan Negeri 6 Surakarta, from August to November 2011. It is qualitative research in the form of ethnography study. The subject of the research was the teaching learning of English at SMK N 6 Surakarta. The data of this thesis were collected from several techniques including observation, interview, and document analysis. In analyzing the qualitative data, the researcher conducted method triangulation to examine the data from interview with the result of the observation, source triangulation to examine the information with the document, and the last is theory triangulation, it is to know the relation among the theories used in this research toward the data research.The teaching learning of English at SMK Negeri 6 Surakarta shows the strength and weaknesses. Some of the strengths are from the student‟s part, they are diligent, attentive, active, risk taker, and cooperative, from the teacher‟s part, they are creative, communicative, supportive and respective, the material and the facilitation used in teaching learning process of English are sufficient enough for carrying out the teaching learning process. However, the teaching learning of English also shows the weaknesses. They are from the student‟s part, it is about the student‟s competency and character, from the teacher‟s part, it covers about teacher‟s ability and intensity of participation in some seminars, trainings and also the short courses, and the last is about the school policy which reduce the time allotment for studying.The research findings of this study imply that teaching learning of English at SMK Negeri 6 Surakarta has been suitable with the theories of English teaching learning, although there were still some weaknesses. Therefore, it is recommended that (1) Institution of Local Education (DISDIKPORA Daerah) should give an addition of the frequency to conduct the seminars, trainings and also the short courses for all teachers, (2) School as the institution to conduct the teaching learning process should give the supervision directly to the educational practitioners, especially to the teachers, (3) The teachers should give much attention to method of teaching learning especially how to design the classroom activity, so the students will not be bored and uninterested, the last (4) the other researchers develop some parts which have not been developed in this research.